Land use sprawl evolution using remote sensing high resolution data based on cellular automata concepts - Mohd. Noor, Norzailawati; Mazlan, Hashim (Malaysian Remote Sensing Society, 2011)
The paper explores a framework combining remote sensing and GIS-cellular automata concepts aimed at improving the modeling of un-authorized land use sprawl. We highlighted that integration in system analysis will lead to new levels of understanding of how urban areas grow and change. Further, we described land use sprawl simulation for the city of Kuantan in Malaysia, in which the urban cellular automata (CA) concept is used. The model for Kuantan city was calibrated and tested with the aid of measured time-series data on land use, through a set of statistical analyses. The fifteen-year simulation until 2015 was run. In essence, the finding is able to predict the spontaneous sprawls of un-authorized land use within conditions stated and can be used to interpret and visualize the dynamic process of urban sprawl locally.